How relevant are economic preferences and personality traits for individual sustainable investment behavior? A framed field experiment - Gunnar Gutsche; Heike Wetzel; Andreas Ziegler (ZBW - Leibniz Information Centre for Economics, 2020)
This paper analyzes the determinants of socially responsible investing (SRI) at the individual investor level. We examine data from an incentivized framed field experiment, which was part of a survey among a representative sample of financial decision makers in German households. Thus, we provide a new approach to elicit preferences for SRI. We further extend the set of potential determinants of SRI and consider all economic preferences according to Falk et al. (2018) and the Big Five personality traits. The analysis reveals that these factors are only of minor relevance in comparison to financial literacy, environmental values, and social norms.
Keywords: G11; Q56; G02; A12; A13; 330; Socially responsible investing; economic preferences; personality traits; framed field experiment